Tinjauan Yuridis Terhadap Efektivitas Pelaksanaan Fungsi Bhayangkara Pembina Keamanan Dan Ketertiban Masyaratakat (Bhabinkamtibmas) Dalam Wilayah Hukum Kepolisian Daerah Kepulauan Riau - Chintya Cen (Journal of Law and Policy Transformation, 2020)
The Community Security and Order is the bearer of community policing in villages. Community Security and Order has objective to carry out preventive functions by directly partnering with the locals, therefore being the tip of the spear of state police in realizing community behavior in line with certain norms to create, maintain and uphold a peaceful, safe and beneficial community environment. The purpose of this study was to determine the effectiveness of Community Security and Order in implementing its functions in Riau Islands Regional Police jurisdiction as regulated in Head of the Indonesian National Police Regulation Number 3 of 2015 about community policing, and Head of the Indonesian National Police Decree Number: KEP/773NII/2016. The effectiveness of Community Security and Order in implementing its duties was reviewed based on the theory of legal effectiveness that coined by Prof. Dr. Soerjono Soekanto. This research was conducted using empirical legal research methods. The author uses primary data obtained from interviews, random sampling of data regarding Community Security and Order activity in Riau Islands Regional Police and activity of Community Security and Order members in each Resort Police within the jurisdiction of Riau Islands Regional Police, as well as conducting observation with a member of Community Security and Order in one of the villages of Batam. Based on the gathered data, the author then processed and compiled it into a comprehensive research report. Research concluded that the implementation of Community Security and Order functions in Riau Islands Regional Police jurisdiction have already been carried in accordance to laws and regulations that is currently in effect. The presence of Community Security and Order helped in shaping community customs to remain positive and maintain a conducive, safe and peaceful environment. However, in overall perspective the implementation of Community Security and Order purposes are not yet fully effective caused by unavailability of specific regulations dictating the functions of Community Security and Order, lack of personnel, as well as limitations in facilitator needs.